Behavior change stages related to physical activity in adolescents from Santa Catarina: prevalence and associated factors - Jaqueline Aragoni da Silva; Kelly Samara da Silva; Adair da Silva Lopes; Markus Vinícius Nahas
Abstract Objective: Verify the prevalence and sociodemographic and economic factors associated with behavior change stages for habitual physical activity practice in adolescents from Santa Catarina. Methods: Secondary analysis of a study on the Behavior of Adolescents from Santa Catarina (CompAC 2). Cross-sectional school-based study of 6,529 high-school students (males, n=2,903) from the state of Santa Catarina public education system in 2011, aged 15 to 19 years. Multinomial logistic regression (crude and adjusted) was used to measure the association. Results: The highest and lowest prevalence rates were found in the maintenance (43.9%) and precontemplation stages (7.0%), respectively. The stages of action, preparation and contemplation showed similar results: 16.2%; 17.0% and 15.6%; respectively. Male adolescents show higher prevalence in the maintenance stage in relation to females and these show a higher prevalence in preparation, contemplation and precontemplation. All the assessed variables (gender, age, area of residence, employment status, family income, maternal education and school grade), with the exception of school shift, were associated with at least one of the stages. Conclusions: A large proportion of adolescents are in the pre-adoption stages and most of these have the intention to start regular physical activity. With the exception of school shift, the assessed variables were associated with stages in different ways, showing different profiles in relation to sociodemographic and economic characteristics in each subgroup.